Perlindungan Anak dalam Perspektif Hukum Islam dan Qanun Aceh Nomor 11 Tahun 2008 - Friatna, Ida (Universitas Islam Negeri Ar-Raniry, 2019)
This paper aims to study child protection in Islamic law perspective, and how the perspective has derived into the Qanun Aceh on child protection. Islamic law discusses child protection as childnurture/safeguards (hadhanah) and custodian (walayah). Child protection means fulfillingchildren's rights and protection from the harmful situation or things that could be a danger to theirphysics, soul, and property. On the national level, the Indonesian government stipulated theUndang-Undang Number 35 Year 2014 on Child Protection, so at the regional level, theGovernment of Aceh followed up by stipulating the Qanun Number 11 Year 2008 on ChildProtection. The Qanun states that child protection aims to ensure the right for life, grow, develop,and participate optimally as well as humanistic value and dignity, and children get protection fromexploitation, violence, and discrimination. Those all protections toward to realize the good quality ofchildren in Aceh, good morality, and wealth. Child protection is conducted through religion, custom,socio-cultural development. It puts forward basic principles, namely anti-discrimination, the child'sneeds-response, the right to live, and appreciation. Substantially, the Qanun contains all rights inprotecting the child. But there are needs in socializing and optimizing the law enforcer in protectingchildren. This study found many indicators on the less of child protection in Aceh. Recently, Acehstands as the third-highest rank province in Sumatera with the number of child violence.Furthermore, children's sexual harassment becomes the most reported case.